Pengaruh Kompetensi Terhadap Kualitas Audit Dimoderasi Etika Auditor - Aditya Dwi Wardhana; Rida Perwita Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to test the competence in influencing audit quality and auditor ethics in moderating the influence of competence on audit quality. This research was conducted at the East Java Provincial Inspectorate Office with a sample of 30 internal auditors. The data collection technique is by distributing questionnaires. The data analysis method in this study uses the Partial Least Square (PLS) approach using the WarpPls 8.0 analysis tool. The results of this study found that competence had a significant effect on audit quality. Auditor ethics can weaken the influence of competence on audit quality. These findings indicate that audit competence in carrying out audits is urgently needed to improve audit quality. Weakening auditor ethics can reduce the influence of competence on audit quality. This research provides important insights for internal auditors in conducting audits by improving the competence of auditors to carry out quality audits.